The effect of the zone and tempo of attack in the attack`s efficacy, in elite female volleyball - Coutinho, P.; Afonso, J.; Mesquita, I. (World Congress of Performance Analysis of Sport VIII, 2008)
In elite women`s volleyball, the attack zone doesn`t interfere with attack efficacy. Castro & Mesquita (2007) concluded the same in a study conducted in high level men`s volleyball. Thus, our initial hypothesis relating the association between these two variables hasn`t found support in our data. A possible explanation may rely on the nature of volleyball. Being a noninvasive sport, the blocker cannot actively steal the ball. Thus being, the spiker has, in almost every situation, the final say in an attack scenario. Possibly, attack efficacy will depend most on the velocity of the game and on the selected spiker. Differently from attack zone, attack tempo has associated with attack efficacy. Namely, quicker attacks (tempo 1) associated with greater attack efficacy, while slower attacks (tempo 3) associated with lower efficacy. This goes according to the commonly accepted concept that the velocity of the attack is a decisive factor in determining attack efficacy (Katsikadelli, 1995; Afonso, Mesquita & Palao, 2005; Mesquita & César, 2007). As such, the strongest variable that must be manipulated by the setter in order to enhance attack efficacy is attack tempo. Nonetheless, this association was not global, and the results require some caution in its analysis. Ultimately, the attack efficacy depends on the spiker`s ability.